ANALYSIS OF CAPITAL FINANCING PRACTICES IN ISLAMIC FINANCIAL INSTITUTIONS - Khalidin, Bismi; Fadhillah. R, Rayhan (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2023)
One of the Sharia financial institutions that contributes effectively to distributing business capital financing is PT. Permodalan Nasional Madani (PNM) through the Fostering a Prosperous Family Economy (PNM Mekaar) program. The practice of capital financing at PNM Mekaar Syariah Aceh Besar uses a joint liability system. The type of research used by the author is qualitative research with data collection techniques using field research, which is research that aims to obtain data that is carried out by going directly into the field related to the focus of the research. To collect data, the techniques used are interviews and documentation. In this study, the author found that in the practice of capital financing carried out by PNM Mekaar, there is no guarantee. If there is one member who does not make PKM (Weekly Group Meeting) installments, then the other group members are responsible for paying off the installments. Therefore, it can be concluded that each member of the group is a guarantee for the other members in paying off the installments.